Comparison of first- and second-line imaging diagnostics (ultrasound + scintigraphy and PET + 4DCT) in visualizing parathyroid glands in primary hyperparathyroidism including ectopic foci - Loryś, Laura; Klimczak, Klaudia; Budzyńska, Kamila; Narloch, Marcin; Kasprzak, Stanisław; Kasprzak, Karolina; Kamiński, Jakub; Kandefer, Norbert (Journal of Education, Health and Sport, 2025)
Introduction: Primary hyperparathyroidism is an endocrine disorder that causes disturbances in calcium and phosphorus metabolism in the human body. The most effective permanent treatment is surgery, which involves the removal of the affected gland. To locate such small glands, various imaging diagnostic methods, including nuclear medicine, are currently used. This study aims to review current imaging protocols for hyperparathyroid glands and compare first- and second-line methods, particularly in cases of ectopic foci. Material and methods: This review was prepared based on articles available on PubMed. The literature review was conducted using the following keywords: primary hyperparathyroidism, primary hyperparathyroidism imaging, primary hyperparathyroidism US, primary hyperparathyroidism MIBI, primary hyperparathyroidism PET/CT, primary hyperparathyroidism 4DCT, ectopic hyperparathyroidism imaging. The current state of knowledge: Primary hyperparathyroidism is a condition that can go unnoticed for an extended period. The diagnosis of the disease is based on laboratory tests, followed by the crucial step of locating the gland responsible for progressively causing damage to the body over time. Identifying the hyperactive gland is essential for performing a successful surgery and curing the patient. However, this often poses a significant challenge, due to the potential for ectopic gland locations. Summary: It is hard to unequivocally state the superiority of one imaging line over the other, as each has specific pros and cons in specific cases. However, in the case of ectopic foci, the 2nd imaging line shows promising results.